2021
DOI: 10.21037/tgh.2020.02.06
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the surgical management of gastric and gastroesophageal junction cancer

Abstract: Since Theodore Billroth and Cesar Roux perfected the methods of post-gastrectomy reconstruction in the late 19 th century, surgical management of gastric and gastroesophageal cancer has made incremental progress. The majority of patients with localized disease are treated with perioperative combination chemotherapy or neoadjuvant chemoradiation. Staging laparoscopy before initiation of treatment or before surgical resection has improved staging accuracy and can drastically inform treatment decisions. The longs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 125 publications
0
3
0
Order By: Relevance
“…However, there is a significant risk of postoperative recurrence. 12 Although the tumor-node-metastasis (TNM) stage might assess the prognosis of AGE, the TNM classification only considers the extent of the tumor, regardless of its biological characteristics or the host’s anticancer response. It will consequently become more crucial to identify a simple, reliable, and repeatable factor that might accurately predict a patient’s prognosis for AGE.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a significant risk of postoperative recurrence. 12 Although the tumor-node-metastasis (TNM) stage might assess the prognosis of AGE, the TNM classification only considers the extent of the tumor, regardless of its biological characteristics or the host’s anticancer response. It will consequently become more crucial to identify a simple, reliable, and repeatable factor that might accurately predict a patient’s prognosis for AGE.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in terms of treatment, although the distance of the tumor epicenters from the gastric cardia varies and thus there is no consensus on the best surgical strategy in clinical practice [29] . However, surgery remains the primary treatment for survival bene ts in patients with CGA and can be effective in improving patient survival [8,30] .…”
Section: Discussionmentioning
confidence: 99%
“…One of the least analyzed types of gastric cancer among the analyzed studies was the LAGC involving the gastroesophageal junction. The study by Narayan et al [43] underscores the shift towards perioperative combination chemotherapy or neoadjuvant chemoradiation for localized disease management, the pivotal role of staging laparoscopy in enhancing staging accuracy, and the consensus favoring D2 lymph node dissection as evidenced by the 15-year follow-up results of the Dutch randomized trial [44]. It was observed that many surgical approaches emerged, such as pylorus-preserving distal gastrectomy for select early-stage gastric cancers and the selective use of multi-visceral resections and cytoreductive surgery with hyperthermic intraperitoneal chemotherapy for locally advanced tumors, marking significant strides in the field's ongoing development.…”
Section: Summary Of Evidencementioning
confidence: 99%